QUADROS SINÓPTICOS E MAPAS DE DIAGNÓSTICOS E DE RECOMENDAÇÕES COMO SUBSÍDIOS PARA A GESTÃO DE EDIFÍCIOS COMPLEXOS: O CASO DE UM MUSEU DE GRANDE PORTE NA CIDADE DE SÃO PAULO - Saft, Juliana Bechara; Zioni, Eleonora; Peixoto, Elaine; Oliveira, Haluane Santana de; Donat, Carmen; Shashiki, Christiane; Ono, Rosaria; Ornstein, Sheila Walbe (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents a discussion on the use of Post-Occupancy Evaluation (POE) combined with risk management applied to a case study of a large museum in a complex historical building located in Sao Paulo City, Sao Paulo. Some qualitative and quantitative instruments of POE were applied to identify the constructive occurrences and the main characteristics of use and occupation. The occurrences were organized into six aspects (signage, maintenance, building pathology, facilities, fire safety and accessibility), correlating them with the agents of deterioration and the degree of risk to the collections. All information was organized into Synoptic Tables and Diagnoses and Recommendations Maps. The use of tables and maps demonstrated to be an efficient strategy for the facilities management (FM) and it can also contribute to the development of the Strategic, Museological and Emergency Planning.